Al2O3-based binders for corrosion resistance optimization of Al2O3–MgAl2O4 and Al2O3–MgO refractory castables. Issue 8 (September 2015) - Tomba Martinez, A.G.; Luz, A.P.; Braulio, M.A.L.; Pandolfelli, V.C.
Abstract: This work addresses the main aspects related to the use of alternative binders [hydratable (HA) or colloidal alumina (ColAlu)] in castables containing different spinel sources (pre-formed or in situ generated), in order to point out: (i) the features that control the corrosion behavior of these materials, and (ii) the key factors to better select a refractory composition. Thermodynamic calculations, corrosion cup-test and SEM analyses were carried out in order to evaluate the slag attack of the designed refractory compositions. According to the attained results, the alumina-based binders (HA or ColAlu) induced a more effective sintering process due to their high specific surface area, improving the physical properties and the binding level of the generated microstructure. The spinel grain size also played an important role in the corrosion behavior of these refractories, as the finer the particles, the greater their dissolution was into the molten liquid, leading to further precipitation of spinel in the solid–liquid interface as a continuous and thick layer. Among the evaluated compositions and considering the presence of silica fume, the most suitable formulation with optimized corrosion resistance was the one with in situ spinel generation and HA as a binder.